A Review on Thiadiazoles - Senthilraja, M. (International Journal of Pharmaceutical & Biological Archive, 2022)
Thiadiazoles has two N-atoms and one sulfur particularly at 1,3,4th position generally exhibits a wide range of pharmacological applications including anti-bacterial, anti-fungal, anti-cancer, anti-depressants, and sugar controlling agents, and also has suppressing effects on diseased part of kidney, lungs, etc. In this article, we provide an elaborate sketch of chemical structures of 1,3,4-thiadiazole moiety including its literatures, synthesis, and biological activities reported so far. As a results, drugs with 1,3,4-thiadiazole are attracted a much attention to the medicinal chemists.